ANALISIS BUDAYA GOTONG ROYONG TERHADAP KERUKUNAN BERAGAMA DI DESA PAMBANG PESISIR - Juliana, Anggun; Gunawan, Feri; Hakimi, Muhammad (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This study aims to explore the influence of gotong royong culture on social harmony and community economic development in Teluk Pambang Pesisir village. The method used is descriptive qualitative with data collection techniques through interviews and observation. The results show that gotong royong culture has a significant influence in strengthening social relationships among community members, building a sense of togetherness, and increasing trust among community members. Through gotong royong activities, communities can build infrastructure and facilities needed to develop the local economy. However, there are still challenges in developing gotong royong culture. Therefore, efforts are needed to strengthen and maintain gotong royong culture so that it can continue to have a positive impact on social harmony and community economic development in Teluk Pambang Pesisir village